Pengaruh Pendidikan Perkoperasian Dan Motivasi Anggota Terhadap Partisipasi Anggota Pada Koperasi Pegawai Republik Indonesia Karpend Lintau Utara - Fatmi Dwi Putri; Jean Elikal Marna (Universitas Negeri Padang, 2022)
The purpose of this study was to determine the effect of cooperative education and member motivation on member participation in the Karpend Lintau Utara Employee Cooperative of the Republic of Indonesia. This is causative research. The population in this study were members of the Karpend Lintau Utara Indonesian Employee Cooperative and the number of samples selected was 95 people and selected using simple random sampling. The data used are primary data obtained through distributing questionnaires to members of the cooperative with predetermined criteria and secondary data from the Karpend Lintau Utara Employee Cooperative of the Republic of Indonesia. The analytical method used is multiple regression analysis with the help of the SPSS 20 program. The results show that (1) cooperative education and member motivation have a significant effect on member participation, (2) cooperative education has a significant effect on member participation, (3) member motivation has a significant influence on member participation. significant to member participation